FV8. Sequential pathology spread in amyotrophic lateral sclerosis: In-vivo evidence from a systematic meta-analysis of structural brain data. Issue 8 (August 2018) - Gorges, M.; Müller, H.P.; Ludolph, A.C.; Kassubek, J.
Abstract : Background: The use of in vivo diffusion tensor imaging (DTI) has substantially improved the understanding of the in vivo cerebral neuropathology of the neurodegenerative disorder amyotrophic lateral sclerosis (ALS) (Filippi et al., 2015 ) as a rapidly progressive neurodegenerative disease with a well-defined neuroanatomical propagation pattern according to the Braak stages (Müller et al., 2016; Kassubek et al., in press ). Objective: Investigation of DTI-based in vivo ALS metadata for the validation of the proposed sequential disease spread in ALS. Methods: A meta-analysis on whole-brain based DTI analysis in ALS patients compared with controls using MEDLINE database was performed. Fifty-five studies, including 1319 ALS patients and 1183 controls, were enrolled. Results: The data analysis demonstrated a characteristic pattern of significant white matter alterations in regions that are known to become sequentially involved. In particular, the hypothesis-guided computation revealed the highest prevalence of significant DTI based alterations in regions associated with stage I followed by stage II and III while the prevalence was demonstrated to be low in regions associated with stage IV. Conclusion: The DTI-based meta-analysis results were in line with present findings of white matter alterations in ALS and support the model of the corticofugal disease spread in four stages and put further in vivo evidence to the proposed ALS staging scheme.